(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2014)
Porous silica materials were synthesized from tetraethyl orthosilicate (TEOS) using Pluronic P123 (non-ionic triblock copolymer, EO20PO70O20) as template under acidic conditions which was then used to prepare polyaniline (PAni) and porous silica composites (PAnisilica) at a fixed molar ratio. These materials were characterized by nitrogen adsorption-desorption isotherm measured by Barrett-Joyner- Halenda (BJH) method and pore size distribution from desorption branch and surface area measured by the Brunauer-Emmett-Teller (BET) method, scanning electron microscopy (SEM), transmission electron microscopy (TEM), TEM-energy dispersive X-ray (EDX) and Fourier transform infrared (FT-IR) spectroscopy. The composite maintains its structure even after the polymerization and the polymer is dispersed on the inorganic matrix. The rod-like porous silica was about 1?m to 1.5 ?m long and on an average the diameter was in the range of 300- 500 nm. The SEM and TEM images show well ordered 2d hexagonal pore, high specific surface area (850 m2g-1) and uniform pore size of ca. 6.5 nm in diameter. After incorporation of PAni inside the silica pore, framework of porous silica did not collapse and the surface area of the composite was as high as 434 m2g-1 which was 5.5 time higher than our previous report of 78.3 m2g-1. Due to shrinkage of the framework during the incorporation of aniline inside the silica, the pore diameter slightly increase to 7.5 nm but still showing Type IV isotherm and typical hysteresis loop H1 implying a uniform cylindrical pore geometry. DOI: http://dx.doi.org/10.3329/bjsir.v49i1.18847 Bangladesh J. Sci. Ind. Res. 49(1), 1-8, 2014